2010
DOI: 10.1007/s10096-010-0896-0
|View full text |Cite
|
Sign up to set email alerts
|

First outbreak of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae in Germany

Abstract: We report the first outbreak of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae in Germany. The presence of KPC was confirmed by polymerase chain reaction (PCR). The KPC-encoding plasmid was analysed by transconjugation experiments, DNA sequencing, Southern blotting and isoelectric focussing. Typing was performed by pulsed-field gel electrophoresis (PFGE). An ertapenem-resistant K. pneumoniae with low minimum inhibitory concentrations (MIC) to other cabapenems (tested by the Vitek system) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 37 publications
0
44
0
5
Order By: Relevance
“…use of gowns/gloves, hand hygiene) may impact on effectiveness. Indeed, the contaminated hands of healthcare staff likely play a key role in the transmission of gram-negative bacteria 58,59 , emphasizing the importance of ensuring optimal compliance. Although all but one of the seven studies (Ben-David et al 2010 39 ) reported attempts to enhance staff knowledge/compliance with infection control measures, few reported on levels of compliance.…”
Section: Key Findingsmentioning
confidence: 99%
“…use of gowns/gloves, hand hygiene) may impact on effectiveness. Indeed, the contaminated hands of healthcare staff likely play a key role in the transmission of gram-negative bacteria 58,59 , emphasizing the importance of ensuring optimal compliance. Although all but one of the seven studies (Ben-David et al 2010 39 ) reported attempts to enhance staff knowledge/compliance with infection control measures, few reported on levels of compliance.…”
Section: Key Findingsmentioning
confidence: 99%
“…The high mortality rate may be attributed to multiple resistance mechanisms that are associated with bla KPC -positive bacteria (21). bla KPC -positive bacteria have been implicated in many cases of hospital-acquired infections, which mandates the rapid detection of these pathogens by the clinical laboratory in order to control their spread (16,20,30). The bla KPC enzymes are encoded in large plasmids that vary in size and structure.…”
mentioning
confidence: 99%
“…In conclusion, KPC-positive K. pneumoniae is an increasing problem in many hospitals in Poland (Baraniak et al, 2009;Zacharczuk et al, 2011), and in other countries near Poland (Hrabák et al, 2011;Richter et al, 2011;Wendt et al, 2010). Many strains are often resistant to all antibiotics except polymyxins and tigecycline.…”
Section: Discussionmentioning
confidence: 92%